2008
DOI: 10.1086/592972
|View full text |Cite
|
Sign up to set email alerts
|

Emergence ofStreptococcus pneumoniaeSerotypes 19A, 6C, and 22F and Serogroup 15 in Cleveland, Ohio, in Relation to Introduction of the Protein‐Conjugated Pneumococcal Vaccine

Abstract: This study documents decreases in the incidence of infections involving vaccine serotypes, increases in infections involving other serotypes, and decreases in the activity of macrolides and clindamycin after conjugate vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 35 publications
4
66
0
2
Order By: Relevance
“…In addition to decreased susceptibility to penicillin, we have also seen decreased susceptibility to erythromycin and TMP-SMX among our serotype 6A and 6C isolates since the introduction of PCV7. Multidrug resistance among serotype 6C isolates increased later in the PCV7 era which is similar to what has previously been reported by others (du Plessis et al, 2008;Jacobs et al, 2008;Rolo et al, 2011a). This increase in resistance to penicillin and multiple other antibiotics among serotype 6C isolates warrants close monitoring as we move into the new era of higher valency conjugate vaccines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition to decreased susceptibility to penicillin, we have also seen decreased susceptibility to erythromycin and TMP-SMX among our serotype 6A and 6C isolates since the introduction of PCV7. Multidrug resistance among serotype 6C isolates increased later in the PCV7 era which is similar to what has previously been reported by others (du Plessis et al, 2008;Jacobs et al, 2008;Rolo et al, 2011a). This increase in resistance to penicillin and multiple other antibiotics among serotype 6C isolates warrants close monitoring as we move into the new era of higher valency conjugate vaccines.…”
Section: Discussionsupporting
confidence: 85%
“…Since then, there have been a number of reports detailing the prevalence, antimicrobial susceptibility patterns, and genetic diversity among serotype 6C isolates collected from both invasive disease and nasopharyngeal colonization studies (Campos et al, 2009;Carvalho et al, 2009;du Plessis et al, 2008;Green et al, 2011;Hermans et al, 2008;Jacobs et al, 2008Jacobs et al, , 2009Nahm et al, 2009;Nunes et al, 2009;Rolo et al, 2011a;Tocheva et al, 2010). In studies that looked at the prevalence of serotype 6C among invasive and carriage isolates, it was found that anywhere between 5% and 100% of isolates that originally typed as 6A were subsequently identified as serotype 6C (Campos et al, 2009;Carvalho et al, 2009;du Plessis et al, 2008;Hermans et al, 2008;Jacobs et al, 2009;Millar et al, 2010;Rolo et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports have shown an increase in pneumococcal infections caused by non-PCV7 serotypes such as 19A, 6C, 22F and 15 [30]. A study in an HIV-infected population from the USA showed an overall decrease in IPD, and that the proportion of PCV7 serotypes significantly decreased despite a slight increase in non-PCV7 serotypes, particularly serotypes 6A and 19A [6].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, they found that this change was present in strains isolated up to 27 years ago and postulated that the 6C capsule type originated more than 27 years ago from a single recombination event in a 6A locus, in which 6A wciN was replaced by a gene of unknown origin. Serotype 6C has subsequently been recognized in several countries and is an important replacement serotype, following the introduction of a conjugate vaccine (3)(4)(5)(6)(7)(8)(9)(10)(12)(13)(14). Recent U.S. surveillance showed a significant 164% increase in the prevalence of invasive disease due to serotype 6C, increasing from 0.22 cases per 100,000 in 1999 to 0.57 and 0.58 cases per 100,000 in 2006 and 2007, respectively, while rates of invasive disease due to serotypes 6A and 6B markedly decreased (3).…”
mentioning
confidence: 99%
“…Serotype 6C has also been shown to be an important, and often antimicrobial-resistant, replacement serotype in countries where the conjugate pneumococcal vaccine containing serotype 6B is used (3,8). The increase in serotype 6C prevalence was recently postulated to be associated with the induction of small amounts of functional anti-6C antibody, compared with anti-6A and anti-6B antibodies, by the conjugate pneumococcal vaccine (12).…”
mentioning
confidence: 99%